A new study on the behavior of pile groups using settlement based design approach - Alver, Ozan; Özden, G. (International Society of Offshore and Polar Engineers, 2016)
In this study, effects of pile length and number of piles on settlement behaviour of pile groups are investigated. It is shown that the settlement of a pile group becomes independent from the number of piles beyond a certain point. Effect of pile length on settlement behaviour of the example foundation is also investigated. It is indicated that the settlement behaviour is becoming more effective in case the pile is longer. Besides, a relationship for group efficiency coefficient is suggested for estimating stiffness of a pile group using single pile stiffness by considering the interaction among piles and non-linear behaviour. © Copyright 2016 by the International Society of Offshore and Polar Engineers (ISOPE).
et al.;ExxonMobil;International Society of Offshore and Polar Engineers (ISOPE);Korea Research Institute of Ships and Ocean Engineering (KRISO);Shanghai Jiao Tong University;SK Innovation
26th Annual International Ocean and Polar Engineering Conference, ISOPE 2016 -- 26 June 2016 through 1 July 2016 -- -- 123420
Keywords: Finite element; Group efficiency; Interaction; Nonlinearity; Pile group